Accounting and development in Africa. (July 2021) - Lassou, Philippe J.C.; Hopper, Trevor; Ntim, Collins
Abstract: Despite accounting being often seen as a crucial ingredient in economic and social development for African countries with pressing needs to meet development challenges (such as alleviating poverty, improving sanitation and public infrastructures, increasing literacy, and improving health), research on African accounting and development is often neglected and relegated to the periphery, especially in leading accounting journals. This Special Issue features a variety of works – theoretically, methodologically, and empirically spanning a wide range of countries across Africa, seeking to redress this and provide avenues and questions for further reflection and future research. In particular, the articles in this Special Issue document the role of accounting in Africa across the private, public and third sectors, and how the role is constrained and compromised by the political economy at play in the continent. The constraints and compromises relate to: (1) external actors, namely international financial institutions, Western governments, international accounting standard setters, Western accounting associations pursuing global growth, and the 'Big 4' accounting firms; and (2) local actors and circumstances, such as domestic governments, weak regulation, low accounting capacity, and webs of corruption. The reported problems with accounting in Africa appear not to reside primarily in accounting per se, but with how it is conceived, implemented and used to achieve particular interests, mostly at the expense of social, economic and institutional development at the domestic level.